image is everything - Elena Grigoryeva (Проект Байкал, 2018)
The word IMAGE has a wide semantic field with diffuse edges. At one edge, this field intercrosses with the meanings of the word VISUALITY. Visual thinking, which is the basis for architecture and other arts, is still the last purely human thing beyond the scope of a computer. The other edge of the field of IMAGE merges into the meaning of BUSINESS REPUTATION, a crucial element of contemporary economy. The image is important for a person, a company, a city, a region and a country and is especially relevant in hard times, in the context of growing competition in the struggle for human assets and investments. The PB Discussion Club touches upon the methods of creation of the image of the city (36). The image of the city is also formed by ICONIC BUILDINGS. Imagine Paris without Eiffel Tower, or New York without Manhattan skyscrapers. How do separate buildings, even the most outstanding and recognizable ones, correlate with the image of the whole city? Such questions are now as relevant as ever for Irkutsk: our city is again in search of the place for the promised Concert Hall for Classical Music initiated by Denis Matsuev (8). A very close, though different, meaning is acquired by IMAGE when we speak about people whose lives intersect with the history of the city. This issue presents the materials devoted to Mark Meerovich. He was one of the most prominent representatives of the Irkutsk architectural school, a world-famous architectural historian, a leading defender of Irkutsk wooden architecture, a writer and a teacher. We cannot leave behind the meanings of IMAGE relating to the problems of self-identification and the sense of national identity and its preservation. The Year of Japan in Russia is represented in the collection of the articles on architecture and architects of our eastern neighbor, which finalizes the main section of this issue (119). While launching the discussion of the IMAGE of cities, we have not embraced all the meanings and shades of this many-sided notion. After all, open questions and ‘To be continued…’ discussions are a part of the image of our journal.